Rogue Wave: Waterfire Saga #2 - Donnelly, Jennifer (Los Angeles ; New York : Disney-Hyperion, 2015)
As Serafina uncovers more clues about the talismans, Neela ventures into a sea dragon's nest, and Ling learns the identity of their foe.
Keywords: Mermaids -- Fiction; Supernatural -- Fiction; Magic -- Fiction; Good and evil -- Fiction